Highly Selective Fluorescent Probe for the Detection of Copper (II) and Its Application in Live Cell Imaging - Zhihao Guo; Xiuji Wang; Pei Wei; Yihua Gao; Qin Li (Journal of Analytical Methods in Chemistry)
The development of fluorescent methods for the detection of metal ions is of great importance due to their diverse environmental and biological roles. Herein, a rhodamine 6G-based off-on fluorescent probe (L1) with a t-butyl pyrrole moiety as the recognition site was designed and synthesized. Photophysical studies show that L1 exhibits excellent sensitivity and selectivity towards Cu2+ to other metal ions in neutral acetonitrile aqueous media. Mechanism studies suggest that the recognition process may associate with a Cu2+ promoted hydrolysis reaction of L1. Furthermore, L1 has been successfully applied in fluorescence imaging of Cu2+ ion in living cells.